Mg + Nb co-doped TiO2 giant dielectric ceramic material and preparation method thereof

By preparing Mg+Nb co-doped TiO2 giant dielectric ceramics, the problems of low dielectric constant, high loss and poor stability of existing high dielectric materials in microelectronic devices have been solved, realizing high-performance giant dielectric materials suitable for the field of microelectronic devices.

CN121779113APending Publication Date: 2026-04-03UNIV OF ELECTRONIC SCI & TECH OF CHINA CHONGQING INST OF MICROELECTRONICS IND TECH +3
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202610009555.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-06
Publication Date
2026-04-03

AI Technical Summary

Technical Problem

Existing high-dielectric materials suffer from problems such as low dielectric constant, high dielectric loss, and poor temperature and frequency stability in microelectronic devices. In particular, BaTiO3 material exhibits a significant phase transition near the Curie temperature, CCTO material has high dielectric loss and poor temperature stability, while Pb-based materials are toxic.

Method used

Mg+Nb co-doped TiO2 giant dielectric ceramics were prepared using the traditional solid-state method. By controlling the properties of TiO2-based materials, TiO2, Nb2O5 and MgO powders were mixed, a binder was added and granulated, pressed into discs and sintered to prepare ceramic materials with high dielectric constant, low dielectric loss and good temperature stability.

Benefits of technology

It achieves giant dielectric properties with high dielectric constant, low dielectric loss and good temperature stability. The material is simple to prepare, low in cost and has good repeatability, making it suitable for the field of microelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121779113A_ABST
    Figure CN121779113A_ABST
Patent Text Reader

Abstract

The invention discloses an Mg + Nb co-doped TiO2 giant dielectric ceramic material and a preparation method thereof, and relates to the technical field of giant dielectric materials. The (Mg + Nb) co-doped TiO2 ceramic is successfully prepared by adopting a traditional solid phase method, the performance of the TiO2-based giant dielectric ceramic is regulated and controlled through a new doping strategy, the raw material is single, the preparation process is simple, the cost is low, the repeatability is good, the yield is high, the obtained ceramic material has giant dielectric performance, and the preparation method is suitable for industrial production. The (Mg + Nb) co-doped TiO2 novel giant dielectric ceramic can meet the requirements of a dielectric material with high dielectric constant, low dielectric loss and good temperature and frequency stability, and compared with other widely applied giant dielectric materials, the titanium dioxide-based giant dielectric ceramic has the characteristics of simplicity in preparation and excellent dielectric property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of giant dielectric materials technology, specifically to a Mg+Nb co-doped TiO2 giant dielectric ceramic material and its preparation method. Background Technology

[0002] In recent years, with the continuous development of electronic information technology, microelectronics technology has begun to play an increasingly important role. As an indispensable part of electronic devices, capacitors are widely used in electronics and energy storage fields.

[0003] With the miniaturization, integration, and high performance of electronic devices, existing high-dielectric materials can no longer meet the practical application requirements of microelectronic devices. There is an urgent need to find dielectric materials with high dielectric constant, low dielectric loss, and high stability. Further research on high-performance dielectric materials will determine the future development potential of electronic devices.

[0004] Materials with a dielectric constant greater than 1000 are called giant dielectric materials, such as BaTiO3 (BTO) and CaCu3Ti4O. 12 NiO, (Pb,La)TiO3 and AFe 0.5 B 0.5 O3 (A=Ba, Sr, Ca; B=Nb, Ta, Sb).

[0005] BaTiO3 giant dielectric material undergoes a significant phase transition near the Curie temperature, resulting in poor temperature and frequency stability, which is detrimental to its large-scale application.

[0006] CCTO materials have a high dielectric constant, but they also have high dielectric loss and poor temperature stability, which remain obstacles to commercial applications.

[0007] (Pb,La)TiO3 materials contain toxic Pb elements in the system, so Pb-based dielectric materials inevitably cause harm to the human body.

[0008] With the continuous optimization of the performance of modern microelectronic devices, the development of dielectric materials with high dielectric constant, low dielectric loss, and good temperature and frequency stability has become an important direction in the field of future electronic devices. Therefore, a new solution is needed to address the above problems. Summary of the Invention

[0009] The purpose of this invention is to provide a Mg+Nb co-doped TiO2 giant dielectric ceramic material and its preparation method, so as to solve the technical problems mentioned in the background art.

[0010] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing Mg+Nb co-doped TiO2 giant dielectric ceramic material, comprising at least the following steps:

[0011] S1: TiO2 powder, Nb2O5 powder and MgO powder are mixed and doped, then zirconia microspheres and alcohol are added, stirred and dried to obtain mixed powder;

[0012] S2: Add a binder to the powder dried in step S1, granulate it, and press it into discs;

[0013] S3: Sinter the discs obtained in step S3 to obtain giant dielectric ceramics.

[0014] Furthermore, the molar fraction of the TiO2 powder is 75 to 95 parts;

[0015] The molar fraction of the Nb2O5 powder is 2.5 to 12.5 parts;

[0016] The molar fraction of the MgO powder is 2.5 to 12.5 parts.

[0017] Furthermore, the stirring speed in S1 is 300 r / min, and the stirring time is 4 h.

[0018] Furthermore, the adhesive is 5% polyvinyl alcohol.

[0019] Furthermore, the pressure at which the disc is pressed is 25 MPa.

[0020] Furthermore, the diameter of the disc is 8mm and the thickness is 2mm.

[0021] Furthermore, the sintering temperature of the disc is 1400℃, and the sintering time is 4h.

[0022] A Mg+Nb co-doped TiO2 giant dielectric ceramic material is prepared by the above-mentioned preparation method of a Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] This invention successfully prepared (Mg+Nb) co-doped TiO2 ceramics using a traditional solid-state method. The performance of TiO2-based giant dielectric ceramics was controlled by a new doping strategy. The raw materials are simple, the preparation process is low-cost, has good reproducibility, and a high yield. All the obtained ceramic materials have giant dielectric properties. Attached Figure Description

[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 The XRD patterns of the Mg+Nb co-doped TiO2 giant dielectric ceramic materials prepared in Examples 1 to 7 of this invention are shown below.

[0027] Figure 2 The images show the SEM images of the Mg+Nb co-doped TiO2 giant dielectric ceramic materials prepared in Examples 1 to 7 of this invention.

[0028] Figure 3 The curves showing the changes in dielectric constant and dielectric loss of the Mg+Nb co-doped TiO2 giant dielectric ceramic materials prepared in Examples 1 to 7 of this invention as a function of frequency at room temperature from 1 kHz to 1000 kHz.

[0029] Figure 4 The temperature stability spectra of the Mg+Nb-doped TiO2 giant dielectric ceramic materials prepared in Examples 1 to 7 of this invention are shown at 1 kHz. Detailed Implementation

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0031] See Figures 1-4 A method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material includes at least the following steps:

[0032] S1: TiO2 powder, Nb2O5 powder and MgO powder are mixed and doped, then zirconia microspheres and alcohol are added, stirred and dried to obtain mixed powder;

[0033] S2: Add a binder to the powder dried in step S1, granulate it, and press it into discs;

[0034] S3: Sinter the discs obtained in step S3 to obtain giant dielectric ceramics.

[0035] The molar fraction of TiO2 powder is 75 to 95 parts;

[0036] The molar fraction of Nb2O5 powder is 2.5 parts to 12.5 parts;

[0037] The molar fraction of MgO powder is 2.5 to 12.5 parts.

[0038] The stirring speed in S1 is 300 r / min, and the stirring time is 4 h.

[0039] The adhesive is 5% polyvinyl alcohol.

[0040] The pressure for pressing into a disc is 25 MPa.

[0041] The disc has a diameter of 8mm and a thickness of 2mm.

[0042] The sintering temperature of the discs was 1400℃ and the sintering time was 4 hours.

[0043] The following are specific examples:

[0044] Example 1:

[0045] Step 1: According to Ti 0.97 (Mg) 0.5 Nb 0.5 ) 0.03 To determine the stoichiometric ratio of O2, 0.1507 g of MgO2 (99.99% purity), 19.3676 g of TiO2 (99.99% purity), and 0.4987 g of Nb2O5 (99.99% purity) were weighed and placed into a container. Zirconium balls were used as grinding balls, and alcohol was used as the grinding medium. The mixture was ball-milled for 4 hours at 300 rpm, dried at 80°C for 12 hours, and passed through a 60-mesh sieve to obtain the raw material mixture.

[0046] Step 2: Add binder to the powder dried in Step 1 and granulate. Place the powder into a stainless steel mold with a diameter of 8 mm and press it into a disc under a pressure of 25 MPa. Heat to 600 °C at a heating rate of 2 °C / min for 3 hours and remove the binder.

[0047] Step 3: Place the cylindrical blank on an alumina plate, place the alumina plate in a tube furnace, heat it to 1000℃ at a heating rate of 10℃ / min, and then heat it to 1400℃ at a heating rate of 5℃ / min. Hold it at this temperature for 3 hours, and then let it cool naturally to room temperature with the furnace to obtain Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0048] Example 2:

[0049] Step 1: According to Ti 0.95 (Mg) 0.5 Nb 0.5 ) 0.05To determine the stoichiometric ratio of O2, 0.2523g of MgO2 (99.99% purity), 18.9682g of TiO2 (99.99% purity), and 0.8308g of Nb2O5 (99.99% purity) were weighed and placed into a container. Using zirconium balls as grinding balls and alcohol as the grinding medium, the mixture was ball-milled for 4 hours at 300 rpm. After drying at 80℃ for 12 hours, the mixture was passed through a 60-mesh sieve to obtain the raw material mixture.

[0050] Step 2: Add binder to the powder dried in Step 1 and granulate. Place the powder into a stainless steel mold with a diameter of 8 mm and press it into a disc under a pressure of 25 MPa. Heat to 600 °C at a heating rate of 2 °C / min for 3 hours and remove the binder.

[0051] Step 3: Place the cylindrical blank on an alumina plate, place the alumina plate in a tube furnace, heat it to 1000℃ at a heating rate of 10℃ / min, and then heat it to 1400℃ at a heating rate of 5℃ / min. Hold it at this temperature for 3 hours, and then let it cool naturally to room temperature with the furnace to obtain Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0052] Example 3:

[0053] Step 1: According to Ti 0.93 (Mg) 0.5 Nb 0.5 ) 0.07 To determine the stoichiometric ratio of O2, 0.3530g of MgO2 (99.99% purity), 18.5691g of TiO2 (99.99% purity), and 1.1628g of Nb2O5 (99.99% purity) were weighed and placed into a container. Using zirconium balls as grinding balls and alcohol as the grinding medium, the mixture was ball-milled for 4 hours at 300 rpm. After drying at 80℃ for 12 hours, the mixture was passed through a 60-mesh sieve to obtain the raw material mixture.

[0054] Step 2: Add binder to the powder dried in Step 1 and granulate. Place the powder into a stainless steel mold with a diameter of 8 mm and press it into a disc under a pressure of 25 MPa. Heat to 600 °C at a heating rate of 2 °C / min for 3 hours and remove the binder.

[0055] Step 3: Place the cylindrical blank on an alumina plate, place the alumina plate in a tube furnace, heat it to 1000℃ at a heating rate of 10℃ / min, and then heat it to 1400℃ at a heating rate of 5℃ / min. Hold it at this temperature for 3 hours, and then let it cool naturally to room temperature with the furnace to obtain Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0056] Example 4:

[0057] Step 1: According to Ti 0.9 (Mg) 0.5 Nb 0.5 ) 0.1 To determine the stoichiometric ratio of O2, 0.5039 g of MgO2 (99.99% purity), 17.9699 g of TiO2 (99.99% purity), and 1.6612 g of Nb2O5 (99.99% purity) were weighed and placed into a container. Using zirconium balls as grinding balls and alcohol as the grinding medium, the mixture was ball-milled for 4 hours at 300 rpm. After drying at 80°C for 12 hours, the mixture was passed through a 60-mesh sieve to obtain the raw material mixture.

[0058] Step 2: Add binder to the powder dried in Step 1 and granulate. Place the powder into a stainless steel mold with a diameter of 8 mm and press it into a disc under a pressure of 25 MPa. Heat to 600 °C at a heating rate of 2 °C / min for 3 hours and remove the binder.

[0059] Step 3: Place the cylindrical blank on an alumina plate, place the alumina plate in a tube furnace, heat it to 1000℃ at a heating rate of 10℃ / min, and then heat it to 1400℃ at a heating rate of 5℃ / min. Hold it at this temperature for 3 hours, and then let it cool naturally to room temperature with the furnace to obtain Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0060] Example 5:

[0061] Step 1: According to Ti 0.85 (Mg) 0.5 Nb 0.5 ) 0.15 To determine the stoichiometric ratio of O2, 0.7556 g of MgO2 (99.99% purity), 16.9716 g of TiO2 (99.99% purity), and 2.4916 g of Nb2O5 (99.99% purity) were weighed and placed into a container. Zirconium balls were used as grinding balls, and alcohol was used as the grinding medium. The mixture was ball-milled for 4 hours at 300 rpm, dried at 80°C for 12 hours, and passed through a 60-mesh sieve to obtain the raw material mixture.

[0062] Step 2: Add binder to the powder dried in Step 1 and granulate. Place the powder into a stainless steel mold with a diameter of 8 mm and press it into a disc under a pressure of 25 MPa. Heat to 600 °C at a heating rate of 2 °C / min for 3 hours and remove the binder.

[0063] Step 3: Place the cylindrical blank on an alumina plate, place the alumina plate in a tube furnace, heat it to 1000℃ at a heating rate of 10℃ / min, and then heat it to 1400℃ at a heating rate of 5℃ / min. Hold it at this temperature for 3 hours, and then let it cool naturally to room temperature with the furnace to obtain Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0064] Example 6:

[0065] Step 1: According to Ti 0.8 (Mg) 0.5 Nb 0.5 ) 0.2 To determine the stoichiometric ratio of O2, 1.0076 g of MgO2 (99.99% purity), 15.9734 g of TiO2 (99.99% purity), and 3.3225 g of Nb2O5 (99.99% purity) were weighed and placed into a container. Using zirconium balls as grinding balls and alcohol as the grinding medium, the mixture was ball-milled for 4 hours at 300 rpm. After drying at 80°C for 12 hours, the mixture was passed through a 60-mesh sieve to obtain the raw material mixture.

[0066] Step 2: Add binder to the powder dried in Step 1 and granulate. Place the powder into a stainless steel mold with a diameter of 8 mm and press it into a disc under a pressure of 25 MPa. Heat to 600 °C at a heating rate of 2 °C / min for 3 hours and remove the binder.

[0067] Step 3: Place the cylindrical blank on an alumina plate, place the alumina plate in a tube furnace, heat it to 1000℃ at a heating rate of 10℃ / min, and then heat it to 1400℃ at a heating rate of 5℃ / min. Hold it at this temperature for 3 hours, and then let it cool naturally to room temperature with the furnace to obtain Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0068] Example 7:

[0069] Step 1: According to Ti 0.75 (Mg) 0.5 Nb 0.5 ) 0.25 To determine the stoichiometric ratio of O2, 1.2598 g of MgO2 (99.99% purity), 14.9750 g of TiO2 (99.99% purity), and 4.1531 g of Nb2O5 (99.99% purity) were weighed and placed into a container. Using zirconium balls as grinding balls and alcohol as the grinding medium, the mixture was ball-milled for 4 hours at 300 rpm. After drying at 80°C for 12 hours, the mixture was passed through a 60-mesh sieve to obtain the raw material mixture.

[0070] Step 2: Add binder to the powder dried in Step 1 and granulate. Place the powder into a stainless steel mold with a diameter of 8 mm and press it into a disc under a pressure of 25 MPa. Heat to 600 °C at a heating rate of 2 °C / min for 3 hours and remove the binder.

[0071] Step 3: Place the cylindrical blank on an alumina plate, place the alumina plate in a tube furnace, heat it to 1000℃ at a heating rate of 10℃ / min, and then heat it to 1400℃ at a heating rate of 5℃ / min. Hold it at this temperature for 3 hours, and then let it cool naturally to room temperature with the furnace to obtain Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0072] Example 8:

[0073] This embodiment proposes a Mg+Nb co-doped TiO2 giant dielectric ceramic material based on the above embodiment, which is prepared by the above-described method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material.

[0074] In summary:

[0075] Mg+Nb co-doped TiO2 giant dielectric ceramics, the general structural formula of which is Ti 1-x (Mg) 0.5 Nb 0.5 ) x O2, where x takes values ​​of 0.03, 0.05, 0.07, 0.1, 0.15, 0.2, and 0.25;

[0076] The novel Mg+Nb co-doped TiO2 giant dielectric ceramic can meet the requirement of "dielectric material with high dielectric constant, low dielectric loss, and good temperature and frequency stability". Compared with other widely used giant dielectric materials, this titanium dioxide-based giant dielectric ceramic has the characteristics of simple preparation and excellent dielectric properties.

[0077] Its dielectric constant and dielectric loss exhibit good temperature and frequency stability.

[0078] When x = 0.05, its dielectric constant is 29458, its loss is 0.102718, and its temperature stability reaches X7.

[0079] Novel Mg+Nb co-doped TiO2 giant dielectric ceramics possess high dielectric constant and low dielectric loss, showing great promise for applications in high-energy-density storage and microelectronics. Reportedly, within the test frequency range of 1000Hz to 1MHz, the dielectric constant of (Mg,Nb) ceramics is greater than 10. 4 The dielectric loss is relatively small. The giant dielectric properties remain basically unchanged within the test temperature range of -25 to 125℃, indicating good temperature stability.

[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

Claims

1. A method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material, characterized in that: At least the following steps are included: S1: TiO2 powder, Nb2O3 powder and MgO powder are mixed and doped, then zirconium oxide microbeads and alcohol are added, stirred and dried to obtain mixed powder; S2: Add a binder to the powder dried in step S1, granulate it, and press it into discs; S3: Sinter the discs obtained in step S3 to obtain giant dielectric ceramics.

2. The method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material according to claim 1, characterized in that: The molar fraction of the TiO2 powder is 75 to 95 parts; The molar fraction of the Nb2O5 powder is 2.5 to 12.5 parts; The molar fraction of the MgO powder is 2.5 to 12.5 parts.

3. The method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material according to claim 1, characterized in that: The stirring speed in S1 is 300 r / min, and the stirring time is 4 h.

4. The method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material according to claim 1, characterized in that: The adhesive is 5% polyvinyl alcohol.

5. The method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material according to claim 1, characterized in that: The pressure at which the disc is pressed is 25 MPa.

6. The method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material according to claim 5, characterized in that: The disc has a diameter of 8 mm and a thickness of 2 mm.

7. The method for preparing a Mg+Nb co-doped TiO2 giant dielectric ceramic material according to claim 1, characterized in that: The sintering temperature of the discs is 1400℃ and the sintering time is 4h.

8. A Mg+Nb co-doped TiO2 giant dielectric ceramic material, characterized in that: The Mg+Nb co-doped TiO2 giant dielectric ceramic material was prepared using any one of the methods described in claims 1-7.

Citation Information

Cited By

  • A rutile single crystal material with magneto-electric anisotropy and a preparation method thereof

    CN122235810A

  • A rutile single crystal material with magneto-electric anisotropy and a preparation method thereof

    CN122235810B